De la façon de nommer aux usages des plantes adventices des cultures en pays Jbala (nord du Maroc) - Louise Clochey; Yildiz Aumeeruddy-Thomas (Revue d'ethnoécologie)
Agriculture, the main economic pillar of the Rif area (Northern Morocco), has remained in the form of an agro-sylvo-pastoral system first and foremost intended for local consumption. This traditional system brings about a patchwork of farming and forestry environments with a very high agro-biodiversity. The purpose of this paper is to show the practices, habits and perceptions related to weeds in agricultural fields in this region —more specifically Ain Mediouna, in Taounate province. Weeds are inseparable from the whole spontaneous flora and it is only by considering the latter in its entirety that our questions might be answered. In fact, an ethnobotanical approach —involving botanical surveys and targeted investigations into the use of spontaneous plants of the agro-ecosystem combined with ethnographic field methods including participant observation and open interviews as well as the extended follow-up of the inhabitants’ activities and relations among themselves - underpins our work. Through corpora collected from elderly and younger women and men as well as children, we analyze the way their knowledge on weeds and more widely spontaneous plants influences their daily lives and various activities, their ties with the agricultural space and with other people. To illustrate our work, we show the whole body of knowledge revolving around (1) cooking a dish of wild leafy vegetables called beqqula and (2) feeding young calves with spontaneous spring plants. Vernacular taxonomies, and more specifically the ways of naming these spontaneous plants, were analyzed. It is to be noted that the way they refer to the natural world is very different from the way cultivated plants are named. How knowledge and practices vary with the inhabitants’ ages and according to specific activities (animal feeding, pastoral pursuits, making food dishes etc.) is also highlighted. Thus the role of spontaneous plants and more precisely of weeds in feeding humans on the one hand, and animals on the other hand, can be dealt with through both cases (beqqula and animal feeding). Moreover, analyzing the practices linked to them, allows an outline of the role played by these plants in the relations between people, and among people and animals, within the investigated territory.